PERSONAL EXPERIENCE ON INVERTED PAPILLOMA SURGICAL TREATMENT (EuroMediterranean Biomedical Journal, 2026)
Inverted papilloma (IP), also known as papilloma Schneideriano or Ewing's papilloma, IS the most common benign epithelial tumor of the paranasal sinuses.It originates from the stroma sub-mucosa of the nasal cavity and paranasal sinuses, and as the name suggests, the papillomatous proliferation of squamous epithelium, instead of producing an exophytic growth, extends into the mucosa and as such is reversed. In this retrospective study we report our experience in the surgical treatment of inverted sinonasal papilloma. The aim of the study was to compare results obtained by endoscopic surgery vs results obtained through open surgery.